2013
DOI: 10.5539/gjhs.v6n2p128
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing the Truth: A Dilemma between Instilling Hope and Respecting Patient Autonomy in Everyday Clinical Practice

Abstract: Background: While medical ethics place a high value on providing truthful information to patients, disclosure practices are far from being the norm in many countries. Transmitting bad news still remains a big problem that health care professionals face in their every day clinical practice.Aims: Through the review of relevant literature, an attempt to examine the trends in this issue worldwide will be made. Method:Various electronic databases were searched by the authors and through systematic selection 51 scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 46 publications
(73 reference statements)
0
48
0
1
Order By: Relevance
“…Kazemi et al evaluated 200 physicians and reported that participants stated that their decision would be dependent on the patient's condition and cultural and social issues (19). The results indicate that truth disclosure varies in different cultures and the extent of information provided to patients is also different depending on their gender, age, cultural and social background and a number of specific factors that are different for each person (20). Thus, when disclosing the truth, personality, culture, religious beliefs, and ethnicity of patients must be taken into account (21).…”
Section: Discussionmentioning
confidence: 99%
“…Kazemi et al evaluated 200 physicians and reported that participants stated that their decision would be dependent on the patient's condition and cultural and social issues (19). The results indicate that truth disclosure varies in different cultures and the extent of information provided to patients is also different depending on their gender, age, cultural and social background and a number of specific factors that are different for each person (20). Thus, when disclosing the truth, personality, culture, religious beliefs, and ethnicity of patients must be taken into account (21).…”
Section: Discussionmentioning
confidence: 99%
“…It is highly relevant for clinical practice ranging from decision making for treatment option to palliative care [2]. There remains a strong resistance against disclosure of diagnosis and prognosis in terminally ill patients, because of the fear of causing despair to patients [3]. Although a protocol for breaking bad news was proposed [4, 5], disclosure practices are far from being the norm in many countries [3], and most of the physicians lacked the essential knowledge and skills for breaking bad news [6].…”
Section: Discussionmentioning
confidence: 99%
“…There remains a strong resistance against disclosure of diagnosis and prognosis in terminally ill patients, because of the fear of causing despair to patients [3]. Although a protocol for breaking bad news was proposed [4, 5], disclosure practices are far from being the norm in many countries [3], and most of the physicians lacked the essential knowledge and skills for breaking bad news [6]. Having a cancer causes psychological problems and cancer patients have higher suicide risk [79].…”
Section: Discussionmentioning
confidence: 99%
“…It is confirmed even in contexts where social practices are traditionally ''protective.'' 9 Thus, the importance of the question does not lie in the claim of an absolute value of autonomy, but as Article 5 of the United Nations Educational, Scientific and Cultural Organization (UNESCO) Declaration of Human Rights and Biomedicine paradigmatically states, in the respect of ''the autonomy of persons to make decisions.'' 10, 11 More precisely, to make decisions that influence one's own end of life within the healthcare system.…”
mentioning
confidence: 99%